Nurses’ Knowledge and Attitude about Intramuscular Injection (LML) - Wafaa M. A. Al-Attar, Wafaa Abd Ali Hattab, Mohammed Faris Abdulghan (Pakistan Journal of Medical & Health Sciences, 2022)
Intramuscular injection, often known as IM, is the injection of a substance into a muscle. In medicine, it is one of the ways to introduce medicine into the body. This method is preferred over some other methods such as intradermal or subcutaneous injection because the muscle has a larger size and has many blood vessels, which speeds up the absorption of the drug in it. The study aims to assess nurses’ knowledge and attitudes on how to use intramuscular injections. A descriptive study was conducted on nurses working in Baghdad hospitals. The study was carried out from 13 January to 10 of July, 2021. An improbable random sample of 200 male and female nurses working in Baghdad hospitals was selected. Data were collected through the use of a designed electronic questionnaire consisting of three parts: Demographic characteristics of nurses, nurses’ knowledge about intramuscular injections, which include 15 items and nurses’ attitudes on the steps for applying intramuscular injection, which include 15 items. An electronic version of the questionnaire was used to collect data from nurses, and the validity and reliability of the questionnaire for the study were determined. The results of the study showed that most of the sample was female 65.5%, (40%) within the age group (20-29 years), (39%) of them graduated from the Medical Institute diploma, 40% of the nurses have experience in the hospital (1-3) And (46%) of them do not have training courses on intramuscular injection. From the results of the research, it was concluded that the majority of the study sample that the nurses’ knowledge about intramuscular injection was of medium of score. While for the nurses’ attitudes on the steps of applying intramuscular injection were highly mean of score. The researchers recommend providing e-learning programs for nurses and nursing students to develop their knowledge experiences as well as their practical skills through continuous training course in hospitals and nursing laboratories.